PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP AJAKAN MEMBELI SAHAM EMITEN OLEH INFLUENCER - Samba Arya Ranu Firmansah (Dinamika, 2022)
ABSTRACTThe increasing number of investors in the capital market, the more parties who want to benefit from the capital market such as influencers who invite their followers on social media to buy shares without material facts and technical or fundamental analysis. The formulation of the problem in this research is is there a ban on invitations to buy shares of issuers for influencers in the capital market?, what is the form of legal protection when invitations to buy shares of issuers by influencers harm investors?. The type of research the author uses is normative law with a statutory approach and a conceptual approach. The legal materials used are primary legal materials, secondary legal materials, tertiary legal materials, for the technique of collecting legal materials it is carried out through library research and analysis of legal materials is carried out in a qualitative descriptive manner. The results of the research obtained by the author are that the prohibition on the invitation of influencers to buy shares of issuers in the capital market has not been regulated in the Capital Market Law, influencers are also not investment advisors and are not capital market supporting professions. The form of legal protection for investors when they feel aggrieved by an invitation by influencers to buy shares of issuers is regulated in the Capital Market Law CHAPTER IX, and OJK also provides two legal protection measures for investors, namely preventive legal protection and repressive legal protection.Keywords: Legal Protection, Investor, Stock, Issuer, InfluencerABSTRAKJumlah investor yang meningkat dipasar modal, semakin banyak pihak yang ingin mendapat keuntungan dari pasar modal seperti influencer yang mengajak pengikutnya di sosial media untuk membeli saham tanpa disertai fakta material dan analisa teknikal maupun fundamental. Rumusan masalah dalam penelitian ini adalah adakah larangan ajakan membeli saham emiten bagi influencer di pasar modal?, bagaimana bentuk perlindungan hukum ketika ajakan membeli saham emiten oleh influencer merugikan pihak investor?. Jenis penelitian penulis gunakan adalah hukum normatif dengan pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conseptual approach). Bahan hukum yang digunakan adalah bahan hukum primer, bahan hukum sekunder, bahan hukum tersier, untuk teknik pengumpulan bahan hukum dilakukan melalui studi pustaka dan analisis bahan hukum dilakukan secara deskriptif kualitatif. Hasil penelitian yang diperoleh penulis adalah larangan mengenai ajakan influencer untuk membeli saham emiten di pasar modal belum diatur dalam UUPM, influencer juga bukan penasihat investasi dan bukan profesi penunjang pasar modal. Bentuk perlindungan hukum bagi investor ketika merasa dirugikan oleh ajakan influencer untuk membeli saham emiten diatur dalam UUPM BAB IX, dan OJK juga memberikan dua upaya perlindungan hukum bagi investor yaitu perlindungan hukum preventif dan perlindungan hukum represif. Kata Kunci : Perlindungan Hukum, Investor, Saham, Emiten, Influencer.